Project Management Knowledge Analysis – A Case of Symptom Checker Development Project - Gunadham, Thanyatida (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Over the past years, emerging technologies have always been crucial for organizations from various industries. Several organizations have implemented new technologies to serve customers’ needs better and be more competitive in the market. Healthcare services are also one of the industries that need to stay up to date with recent technologies. Therefore, they can apply these technologies to their information systems projects. This paper aims to discuss a case of symptom checker development project carried out in a hospital in Thailand. Project management knowledge areas applied in the project are also identified from the activities performed in the project. Moreover, the main problems that occurred during the project were addressed along with the recommendations for solving the problems. The findings suggest that organizations apply only some project management knowledge areas from the framework. Those are project scope management, project procurement management, project integration management, project schedule management, project quality management, and project communication management.